2013
DOI: 10.1017/s095026881300280x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of air samples, nasal swabs, ear-skin swabs and environmental dust samples for detection of methicillin-resistantStaphylococcus aureus(MRSA) in pig herds

Abstract: To identify a cost-effective and practical method for detection of methicillin-resistant Staphylococcus aureus (MRSA) in pig herds, the relative sensitivity of four sample types: nasal swabs, ear-skin (skin behind the ears) swabs, environmental dust swabs and air was compared. Moreover, dependency of sensitivity on within-herd prevalence was estimated. spa-typing was applied in order to study strain diversity. The sensitivity of one air sample was equal to the sensitivity of ten pools of five nasal swabs and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…It has previously been used for various types of housed poultry (6,20), as well as other farmed animals (1). Moreover, the flock contamination status for multiple bacterial pathogens could potentially be determined simultaneously by this form of air sampling (24), as evaluated by others, e.g., to test for bioterror-related microorganisms (11) and to monitor the quality of indoor air (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been used for various types of housed poultry (6,20), as well as other farmed animals (1). Moreover, the flock contamination status for multiple bacterial pathogens could potentially be determined simultaneously by this form of air sampling (24), as evaluated by others, e.g., to test for bioterror-related microorganisms (11) and to monitor the quality of indoor air (13).…”
Section: Discussionmentioning
confidence: 99%
“…The objective of this study was to assess the use of filter-based air sampling coupled with qPCR, using nonproprietary, open-formula methods and devices (1,6,20), for quantitative monitoring of Campylobacter in poultry houses as an alternative to collecting and analyzing boot swab samples. Three chicken (Gallus gallus) flocks in Poland were included, and air and boot swabs were sampled in parallel throughout an 8-week period.…”
mentioning
confidence: 99%
“…Several studies have investigated the occurrence of MRSA in the air and on soil surfaces of pig barns. Most studies reported a low prevalence of LA-MRSA in air samples, nevertheless, the presence of MRSA in air samples may contribute to the spread of this strain in the natural environment [107][108][109][110].…”
Section: Antibiotic Resistance In the Environmentmentioning
confidence: 99%
“…), the AirPort MD8‐sampler for 15 min (Agersø et al . ), the ASCI for 4–20 min (Madsen et al . ) and the Respicon for 3 h (Madsen et al .…”
Section: Introductionmentioning
confidence: 99%
“…Different sampling times are used for sampling airborne MRSA, for example EDCs sampled for 2 weeks (Dorado-Garcia et al 2013) and up to 7 days (Feld et al 2018), impingers for 30 min , IOM for 150 min , GilAir5 and GSP samplers for 6-10 h (Gilbert et al 2012) and for 5-8 h (Graveland et al 2012), GSP for 1 h (Angen et al 2017), the AirPort MD8-sampler for 15 min (Agersø et al 2013), the ASCI for 4-20 min (Madsen et al 2018a) and the Respicon for 3 h (Madsen et al 2018a) on animal farms and in a pig slaughterhouse. The samples are treated differently after sampling.…”
Section: Introductionmentioning
confidence: 99%